Philological Insights in Qur'an and Tafsir Education: A Framework for Developing Teaching Materials - Shofaussamawati, Shofaussamawati; Khusniyah, Aziizatul; Setyaningsih, Enggelina Oka; Kuzairi, Muhammad (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
This research explores the potential for integrating philological methods into the development of the Quran's teaching material and manuscript-based interpretations. The study aims to compile in-depth and authentic educational material using ancient manuscripts as primary sources. The methods used included textual and contextual analysis of the manuscripts of the Qur'an and interpretations of the classical period, which were chosen through a rigorous curation process. The results of this study show that the integration of philology not only enriches the content of the teaching material but also improves the student's conceptual and historical understanding of classical texts. Furthermore, this article discusses the challenges and solutions in translating and adapting the contents of manuscripts into pedagogical formats suitable for modern classrooms. This research has made important contributions to the teaching methods of the Qur'an and to a more dynamic and historical evidence-based interpretation.